(untitled) (International Educators Conference, 2025)
This study investigates the linguistic and cultural challenges encountered when translating somatic phraseological units (body-related idioms) from English into Uzbek. Phraseological expressions are often culturally embedded and difficult to render without loss of meaning or stylistic nuance. The paper explores the equivalence of phraseological expressions, the problem of polysemy, and contextual shifts, while highlighting strategies such as full and partial equivalence, antonymic translation, and descriptive rendering. Findings demonstrate that translation of such units demands a nuanced understanding of both source and target languages’ idiomatic inventories and their socio-cultural contexts.